PELAKSANAAN KEMITRAAN ANTARA SEKOLAH, KELUARGA, DAN MASYARAKAT PADA SMK BISNIS MANAJEMEN KOTA SURAKARTA - Jatmika, Surya (Jurnal Pendidikan Ilmu Sosial, 2018)
This study aims to get information about the implementation of the partnership programs for school, family, and community at SMK Negeri 1 Surakarta. This study was case study research with qualitative approach that was equipped quantitative data (percentage). The research subjects consisted of 5 people, namely the teacher, principal, school committee, and two students. Data collection techniques used are interviews, observation, and documentation. Testing the validity of the data are done by triangulation method which not only collects data but also tests the credibility of the data obtained. The data were analyzed using the qualitative data analysis and percentage descriptive statistics. The results of the study are as follows. (1) Generally, the process of preparing partnership programs for school, family, and community at SMK Negeri 1 Surakarta is not accordance with the guidelines issued by the Indonesia Ministry of Education and Culture. The school does not have a plan and organizing system related to school, family and community partnership programs. (2) The level of implementation of the partnership program is 82.5%, schools tend to focus on utilizing existing institutions such as the role of school committees so that there is no variation in parental involvement activities in the learning process and activities in the school environment.